Strobilanthes sripadensis, a new species of Acanthaceae from Sri Lanka - Nilanthi, Rajapakse Mudiyanselage Renuka; Gopallawa, Bhathiya; Jayawardana, Nuwan; Jayasinghe, Himesh Dilruwan (Phytotaxa, 2023)
Strobilanthes sripadensis, a new species of Acanthaceae from Peak Wilderness Nature Reserve, Sri Lanka is described and illustrated. Both morphological and palynological evidence clearly indicate that S. sripadensis is a distinct species. The new species is closely related to S. pentandra, but differs by having short acuminate leaf apex, entire or slightly sinuate leaf margin, 5–7 pairs of lateral veins, outermost bract longer than the inner one, bract, bracteole, and calyx pubescent, white corolla with prominent dark purple lines at throat and fertile stamens 4.The full description, line drawings, photographs, and information on habitat and ecology, distribution, phenology are also provided. It is accessed to be Critically Endangered according to the IUCN Red List categories and criteria.